Triple points and phase diagrams of Born-Infeld AdS black holes in 4D Einstein-Gauss-Bonnet gravity - Chao-Ming Zhang (Physics Letters B, 2020)
By treating the cosmological constant as a thermodynamic pressure, we investigate the thermodynamic behaviors of Born-Infeld AdS black hole in 4D Einstein-Gauss-Bonnet (EGB) gravity. The result shows that the Van der Waals like small/large black hole (SBH/LBH) phase transition always appears for any positive parameters α and β. Moreover, we observe a new phenomenon of small/intermediate/large black hole (SBH/IBH/LBH) phase transition with one tricritical and two critical points in the available parameter region for α and β. This behavior is reminiscent of the solid/liquid/gas phase transition.